2021
DOI: 10.1186/s13054-021-03701-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of prehospital tranexamic acid on mortality and transfusion requirements: match-pair analysis from the nationwide German TraumaRegister DGU®

Abstract: Background Outcome data about the use of tranexamic acid (TXA) in civilian patients in mature trauma systems are scarce. The aim of this study was to determine how severely injured patients are affected by the widespread prehospital use of TXA in Germany. Methods The international TraumaRegister DGU® was retrospectively analyzed for severely injured patients with risk of bleeding (2015 until 2019) treated with at least one dose of TXA in the preho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
26
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 50 publications
3
26
0
5
Order By: Relevance
“…Although concerns about CRASH-2 design and methodology persist [ 94 ], the results of the study became widely accepted as definitive, and TXA became recognized as the “anti-hemorrhage” drug carried on many ambulances and medical helicopters [ 95 ]. In fact, data confirm the effectiveness of TXA when selectively administered to seriously injured patients (mean ISS ≥ 30) during the prehospital phase of care [ 96 , 97 ].…”
Section: Management Of the Polytrauma Victimmentioning
confidence: 81%
“…Although concerns about CRASH-2 design and methodology persist [ 94 ], the results of the study became widely accepted as definitive, and TXA became recognized as the “anti-hemorrhage” drug carried on many ambulances and medical helicopters [ 95 ]. In fact, data confirm the effectiveness of TXA when selectively administered to seriously injured patients (mean ISS ≥ 30) during the prehospital phase of care [ 96 , 97 ].…”
Section: Management Of the Polytrauma Victimmentioning
confidence: 81%
“…We would like to thank Honore et al for their critical appreciation of our work. They have legitimately dealt with the potential main confounder of our study [1]. The aim of our work was to investigate the effects of preclinical administration of TXA in severely injured patients (ISS TXA 32.4 SD 14.7, Control 32.0 SD 14.7) in a developed healthcare system.…”
Section: Response To Letter: Study Conclude That Txa In Severely Injured Was Associated With Lower Mortality: Beware Of Potential Confounmentioning
confidence: 99%
“…With great interest, we read the recently published article by Imach et al who concluded that tranexamic acid (TXA) use in severely injured patients was associated with a significantly lower risk of massive transfusion and lower mortality in the early in-hospital treatment period, based on matched pairing using the nationwide German Trauma Register DGU® [ 1 ]. When comparing the data between the two groups (with and without TXA), we observe that patients receiving TXA received significantly more hemostatic agents than the non TXA group (47.8% vs 44.2%, p value = 0.018) [ 1 ]. Hemostatic agents comprised fibrinogen, prothrombin concentrates (PPSB), calcium, factor VII or factor XIII which are all major players in coagulation after severe trauma, particularly fibrinogen [ 1 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations